Post-capital a reader - Cotton, Michelle (Mousse Publishing, 2021)
This richly illustrated volume documents works of sculpture, painting, photography, video, and performance by more than twenty artists from different parts of the world, all addressing production, consumption, and wealth. The images cohabit with excerpts from longer texts by some of today's most influential thinkers on the subject of our digital age, its consequences concerning human freedoms, and the largely invisible dynamics that are driving an evolving and unequal world order.
Imprint: "Post-Capital: A Reader" is published on the occasion of the exhibition "Post-Capital. Art & the Economics of the Digital Age", 02 October 2021 - 16 January 2022, Mudam Luxembourg - Musée d'Art Moderne Grand-Duc Jean; 17 September 2022 - 15 January 2023, Kunsthal Charlottenborg, Copenhagen
Keywords: Armut; Verbrauch; Reichtum; Globalisierung; Kunst; Ausstellungskatalog -- Musée d'Art Moderne Grand-Duc Jean -- 02.10.2021-16.01.2022 -- Luxemburg, Stadt; Ausstellungskatalog -- Kunsthal Charlottenborg -- 17.09.2022-15.01.2023 -- Kopenhagen